Bumiputera, Malays and Islam in the Politicization of the New Economic Policy - Maznah Mohamad (Kajian Malaysia, 2003)
The purpose of this papcr is to revisit thc New Economic Policy (NEP) u. u i""hno"ratic doctrine and to assess whether it was through the NEP that Malaysia was able to achieve cconomic growth and ethnic peace. In ordcr to guide this exercise, I will posc several questions: Was the NEP fllly ancl consistcntly implemented as it was conceived?, Did the implementation of the policy go tlirough a linear and progressivcoursc'?, What were the cxtraneous factors affecting the course and discourse of the NEP?, How does oncmcasure the successes and failures of the NEP,there were an Y?, If thc formal phase of the NEP had terrninated, does it still exist today in a variant form or in an infonnal but pcrvasive nature.